War on terabytes. (Economist, 2013)
The article discusses cybersecurity in the banking industry, with particular focus given to threats posed to banks and financial systems by hackers. Distributed denial of service (DDOS) attacks undertaken against banks including JPMorgan Chase, Wells Fargo, and Citigroup are examined, and discussion of whether banks or governments should be responsible for increasing online security to prevent further attacks is offered.